Відображення проблеми конформізму у кінематографі - Теребій, І. Д. (ХНУРЕ, 2025)
This work is devoted to the study of the problem of conformism in cinema. For analysis were taken several different films from different decades and genres, in which conformism is presented from different points of view, revealing its positive and negative impact on both society and the characters shown in the film.
Keywords: конформізм у кінематографі; кінематограф